Enhanced light emission in vertical-structured GaN-based light-emitting diodes with trench etching and arrayed p-electrodes. (May 2015) - Lin, Tseng-Hsing; Wang, Shui-Jinn; Tu, Yung-Chun; Hung, Chien-Hsiung; Lin, Che-An; Lin, Yung-Cheng; You, Zong-Sian
Graphical abstract: Highlights: Enhanced WPE of VLEDs using trench etching and arrayed p-electrodes is reported. Calculated and experimental results justify the effect of the proposed scheme. Trench design enhances light emission through releasing total internal reflection. Arrayed p-electrodes improve current spreading of the proposed VLED. Enhancement in WPE of VLED with a 2 × 2 array by 2.79% at 364.4 mA/mm 2 is obtained. Abstract: We investigate the effect of trench etching and arrayed p-electrodes in improving current spreading and the efficiency of light extraction of GaN-based vertical-structured light-emitting diodes (VLEDs). Both simulated and experimental results on the uniformities of current distribution and light emission are presented and discussed. For a 2 × 2 array VLED with a die size of 1020 × 1020 μm 2, enhancements in light output power by 0.38% (6.03%) and wall-plug efficiency by 2.79% (2.32%) at 364.4 mA/mm 2 (728.9 mA/mm 2 ) as compared with that of regular VLED are achieved experimentally, which are attributed to improved current spreading from the arrayed p-electrode and trench designs as well as enhanced light emission from the trench region.